Modulation of Nerve Cell Differentiation: Role of Polyphenols and of Contactin Family Components - Picocci, Sabrina; Bizzoca, Antonella; Corsi, Patrizia; Magrone, Thea; Jirillo, Emilio; Gennarini, Gianfranco (Frontiers in Cell and Developmental Biology, 2019)
In this study the mechanisms are explored, which modulate expression and function of cell surface adhesive glycoproteins of the Immunoglobulin Supergene Family (IgSF), and in particular of its Contactin subset, during neuronal precursor developmental events. A specific concern is on the significance of the expression profile of such molecules and on their ability to modulate signalling pathways activated through nutraceuticals, in particular polyphenols, administration. Both in vitro and in vivo approaches are used. As for the former, by using the human SH-SY5Y neuroblastoma line, grape seed polyphenols effects are evaluated on proliferation and commitment/differentiation events along the neuronal lineage. In SH-SY5Y cell cultures, polyphenols were found to counteract precursor proliferation and to promote their differentiation, as deduced from studying their developmental parameters, including expression of cell cycle and neuronal commitment/differentiation markers as well as by measuring neurite growth. In such cultures, Cyclin E expression and BrdU incorporation were downregulated, indicating reduced precursor proliferation while increased neuronal commitment/differentiation were inferred from upregulation of cell cycle exit (p27-Kip) and neuronal commitment (β-tubulin) markers as well as by measuring neurite length through morphometric analysis. The polyphenol effects on precursor developmental parameters were also explored in vivo, in developing cerebellar cortex, by using as a model the TAG/F3 transgenic mice, which undergo delayed neural development as a consequence of Contactin 1 adhesive glycoprotein upregulation and premature expression under control of the Contactin 2 gene (Cntn-2) promoter. In this transgenic line, a Notch pathway upregulation is known to occur and polyphenol treatment was found to counteract such an effect, demonstrated through downregulation of the Hes-1 transcription factor. Polyphenols also downregulated the expression of adhesive glycoproteins of the Contactin family themselves, demonstrated for both Contactin 1 and Contactin 2, indicating the involvement of changes in the expression of the underlying genes in the observed phenotype. These data support the hypothesis that the complex control exerted by polyphenols on neural development implies modulation of expression and function of cell adhesion molecules of the Contactin family and of the associated signalling pathways, indicating potential mechanisms whereby such compounds modulate neurogenesis.